The inhibition rate estimated using VerifyNow can help to predict the thromboembolic risk of coil embolization for unruptured intracranial aneurysms. (24th August 2021) - Kim, Young Deok; Kwon, O-Ki; Ban, Seung Pil; Won, Yu Deok; Bang, Jae Seung; Kim, Tackeun; Lee, Si Un; Jo, Hyun Jun; Oh, Chang Wan
Abstract : Background: The role of the inhibition rate of VerifyNow in assessing the thromboembolic risk of coil embolization for unruptured intracranial aneurysms is unclear. Objective: To carry out a retrospective study to determine whether the inhibition rate could provide additional help in predicting thromboembolic events when it was used for patients with a P2Y12 reaction unit (PRU) level of 220 or lower. Methods: Patients who underwent coil embolization for unruptured aneurysms with an appropriate PRU level (PRU 220 or lower) between January 1, 2015 and December 31, 2018 were analyzed. A total of 954 patients with 1020 aneurysms were included in this study. The primary outcome was the thromboembolic events occurring within 30 days after coil embolization. The receiver operating characteristic (ROC) curve and the area under the curve (AUC) were obtained to determine the quantitative predictive ability of the inhibition rate. The optimal cut-off value was derived using the Youden index. Results: Thromboembolic events developed in 11 patients (1.08% of 1020 procedures). The AUC of the ROC curve was 0.83. The optimal cut-off value of the inhibition rate derived using the maximum Youden index was 22.0%. A sensitivity test using a multiple logistic regression analysis demonstrated that the inhibition rate was a significant variable for predicting thromboembolic events. Conclusions: The inhibition rate can be used to determine high thromboembolic risks for patients with PRU levels of 220 or lower. The optimal cut-off value of the inhibition rate was 22.0% when the PRU level was 220 or less.